Fecal microbiota transplantation for hypertension: an exploratory, multicenter, randomized, blinded, placebo-controlled trial - Luyun Fan; Junru Chen; Qi Zhang; Jie Ren; Youren Chen; Jinfeng Yang; Lu Wang; Zihong Guo; Peili Bu; Bingpo Zhu; Yanyan Zhao; Yang Wang; et al. (Microbiome)
Abstract Background On the basis of the contribution of the gut microbiota to hypertension development, a novel strategy involving fecal microbiota transplantation (FMT) has been proposed to treat hypertension, but its efficacy has not been investigated in the clinic. Methods In a randomized, blinded, placebo-controlled clinical trial (2021/03–2021/12, ClinicalTrials.gov, NCT04406129), hypertensive patients were recruited from seven centers in China, and received FMT or placebo capsules orally at three visits. The patients were randomized at a 1:1 ratio in blocks of four and stratified by center by an independent statistician. The intention-to-treat principle was implemented, as all randomized participants who received at least one intervention were included. The primary outcome was the decrease in office systolic blood pressure (SBP) from baseline to the day 30 visit. Adverse events (AEs) were recorded through the 3-month follow-up to assess safety measures. Alterations in BP, the fecal microbiome, and the plasma metabolome were assessed via exploratory analyses. Results This study included 124 patients (mean age 43 years, 73.4% men) who received FMT (n = 63) or placebo (n = 61) capsules. The numbers of participants who experienced AEs (13 (20.6%) vs. 9 (14.8%), p = 0.39) and the primary outcome (6.28 (11.83) vs. 5.77 (10.06) mmHg, p = 0.62) were comparable between the groups. The FMT group presented a decrease in SBP after 1 week of FMT, with a between-arm difference of − 4.34 (95% CI, − 8.1 to − 0.58; p = 0.024) mmHg, but this difference did not persist even after repeated intervention. After FMT, shifts in microbial richness and structure were identified and the abundance of the phyla Firmicutes and Bacteroidetes was altered. Decreases in the abundances of Eggerthella lenta, Erysipelatoclostridium ramosum, Anaerostipes hadrus, Gemella haemolysans, and Streptococcus vestibularis and increases in the abundances of Parabacteroides merdae, Prevotella copri, Bacteroides galacturonicus, Eubacterium sp. CAG 180, Desulfovibrio piger, Megamonas hypermegale, Collinsella stercoris, Coprococcus catus, and Allisonella histaminiformans were identified and correlated with office SBP. Those species were also correlated with responding and inversely office SBP-associated metabolites including tyrosine, glutamine, aspartate, phenylalanine, methionine, serine, sarcosine, and/or asparagine. Conclusions Safety but unsustainable BP reduction was observed in the first trial of the effects of FMT on hypertension. Additional intervention studies on specific microbes with metabolite-targeting and BP-modulating features are needed. Video Abstract